PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Chandra, Jessica Madeline; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2025)
The objective of this study is to specify the impact of dividend policy, profitability, and leverage on firm value in primary consumer goods sector companies in 2019-2021. The sample was picked out by purposive sampling method and the legitimate data is 73 data. The technique of processing data uses multiple regression analysis supported by the SPSS (Statistical Product and Service Solution) Version 25 program. This study has the outcomes pointed out that dividend policy has a significant and positive impact on firm value, profitability has no significant and negative impact on firm value, and leverage has no significant and positive impact on firm value. The implication of this research is that companies need to pay attention to the company's dividend policy, profitability, and leverage in order to provide a positive signal to investors so can increase firm value.